Against Prevailing Currents: The History of Them Days Magazine in Labrador - Hallett, Vicki S. (Acadiensis, 2019)
For more than four decades, Them Days magazine has portrayed Labradorians in their own words through publishing a quarterly periodical and multiple books about Labrador as well as creating a public archive. This article will focus on the historical aspects of the magazine’s inception and the challenges its creators faced as they built a storehouse of Labrador narratives that would represent the cultures that make Labrador unique and document a way of life considered to be in precipitous decline. It will also discuss how individuals, peoples, and even magazines must continually negotiate their identities through power relations in a settler-colonial state.